2001
DOI: 10.4269/ajtmh.2001.65.518
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and seasonality of cryptosporidiosis in a small rural village occupied predominantly by aged people in the Republic of Korea.

Abstract: Abstract. The prevalence of Cryptosporidium parvum infection and its seasonality were studied in a small rural village occupied predominantly by aged people in Hwasun-gun, Chollanam-do, Republic of Korea. Fecal samples were collected monthly from November 1996 to October 1997 and examined for enteric parasites. To detect oocysts of C. parvum, the modified acid-fast stain was applied. To determine effects of climatic factors, local weather reports were collected. The overall oocyst prevalence during 1 year was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
32
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 24 publications
6
32
2
Order By: Relevance
“…Additionally, youngest children tend to have relatively more symptomatic disease than older [23]. The rate of infection in the present study is similar to other studies [24,25].…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, youngest children tend to have relatively more symptomatic disease than older [23]. The rate of infection in the present study is similar to other studies [24,25].…”
Section: Discussionsupporting
confidence: 83%
“…The difference in the results can be associated with the number of samples taken, methodology, environmental differences and The prevalence observed for Cryptosporidium spp. in the elderly was lower than the ones presented on research 7,21,24 . Factors affecting the survival and the number of oocysts present in the environment, such as rain or agricultural practices, can interfere with differences in the prevalence of that protozoan.…”
Section: Discussioncontrasting
confidence: 45%
“…Age did not present any correlation with the presence of Cryptosporidium spp., but is an important factor 7,21 . The elderly are more susceptible to having serious illnesses with age advancement, and these diseases can present longer duration thereby increasing the chance that individuals may have higher rates of secondary infections, such as enteroparasitosis 9 The origin of the institution where the elderly lived was important only when associated with G. duodenalis, and there is no basis of explanation for this association.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Kenya also documented increased oocyst contamination of surface waters at the end of the rainy season, which was consistent with the timing of human infections in the region (20). However, cryptosporidiosis has been reported to occur in the spring season in South Korea (6), in the summer and autumn months in Israel (12), and in the cooler months of November to April in Kuwait (28). Differences in seasonality from different geographical areas can be explained by a recent meta-analysis of seasonality of cryptosporidiosis that found that increases in temperature and rainfall were predictors of increased cryptosporidiosis.…”
Section: Discussionmentioning
confidence: 54%